METODE MENDONGENG UNTUK MENANAMKAN BUDI PEKERTI ANAK USIA DINI KELOMPOK B1 TK MASYITHOH WELAHAN WETAN - Titik Kadarsih; Utami Budiyati (JURNAL WARNA, 2023)
The Storytelling Method to Instill Character in Early Childhood in Group B1 of Masyithoh Welahan Wetan Kindergarten in the 2021-2022 Academic Year is one of the methods used in Group B1 of Masyithoh Welahan Wetan Kindergarten to instill character in early childhood in Group B1. The purpose of this study was to determine the method of storytelling to instill character in early childhood in the B1 group of Masyithoh East Welahan Kindergarten for the 2021-2022 academic year. This research uses the type of field research (Field Research). The research approach used is a qualitative descriptive approach. Data collection techniques were carried out using observation, interviews, and documentation. The subjects in this study were children of Group B1 TK Masyithoh Welahan Wetan. The results of the study can be concluded that the storytelling method is one of the methods used to instill character in early childhood in Group B1 TK Masyithoh Welahan Wetan. The benefits of the storytelling method include: bringing children closer to their environment, the relationship between children and teachers will be closer. The storytelling method develops the ability of religious and moral values, social emotional, language, cognitive, and physical motoric. The storytelling method will train children to be good listeners. The storytelling method develops children's fantasies. The storytelling method fosters children's interest in reading. The storytelling method is one of the learning media. The results of the percentage assessment of the cultivation of character for early childhood in group B1 TK Masyithoh Welahan Wetan obtained an average of 87.44% Very Well Developed (BSB) and an average of 12.56% Developed as Expected (BSH).